ANALYSIS OF THE REHABILITATION PROCESS AT WOMEN’S CORRECTIONAL FACILITY CLASS IIA TANGERANG - Ayu, Meissy Dwi; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to explore the implementation of inmate rehabilitation programs at Women’s Correctional Facility Class IIA Tangerang, identify challenges, evaluate the applied assessment system, and uncover the expectations of the inmates. Using a qualitative approach, data were obtained through in-depth interviews with inmates. Findings reveal that rehabilitation programs include practical skills training, personality development, and spiritual growth, fostering holistic development among inmates. However, challenges such as limited facilities, program relevance, and staff competency hinder optimal implementation. Program evaluations are deemed less transparent, though they significantly motivate inmates to improve. Inmates hope for improved facilities, more relevant programs, and a personalized approach to rehabilitation. This study concludes that rehabilitation programs have significant potential for positive change but require quality improvements and enhanced resource support for better outcomes. Keywords: Rehabilitation; Women’s Correctional Facility; Inmate Expectations